Single Commercially Available Integrated Circuit-based Sinusoidal Oscillators with Amplitude Adjustability and Electronic Control of Condition - Suleeporn Duangkaew; Piya Supavarasuwat; Montree Siripruchyanun; Roman Šotner; Winai Jaikla; Wisuit Sunthonkanokpong (Istanbul University - Journal of Electrical & Electronics Engineering, 2024)
Abstract This paper presents four new sinusoidal oscillators using a commercially available integrated circuit (IC). The proposed circuits are simple topologies that employ a single commercial IC, LT1228. It is connected to passive element, consisting of four resistors and two capacitors. All derived oscillator circuits have low output impedance, allowing them to connect to other circuits without requiring an additional buffer. Using an active LT1228 device enables electronic adjustment of parameters in the proposed circuits. A feedback resistor can be used to change the output signal's amplitude without affecting the oscillation's frequency or condition. We performed both simulations using the PSPICE program and experiments to confirm the accuracy of all proposed oscillator circuits. The best total harmonic distortion was 0.13% for the proposed oscillator circuit 3. Adjusting the maximum amplitude using a resistor provides a gain of roughly 1.5–16.5 dB for the proposed oscillator circuit no. 1. Cite this article as: S. Duangkaew, P. Supavarasuwat, M. Siripruchyanun, R. Sotner, W. Jaikla and W. Sunthonkanokpong, "Single commercially available integrated circuit-based sinusoidal oscillators with amplitude adjustability and electronic control of condition," Electrica, 24(3), 799-811, 2024.
Keywords: Advanced Adaptive Filtering Techniques; Sensor Technology and Measurement Systems; Analog and Mixed-Signal Circuit Design